2021
DOI: 10.3389/fimmu.2020.580334
|View full text |Cite|
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Capsid Protein VP1 Antagonizes TPL2-Mediated Activation of the IRF3/IFN-β Signaling Pathway to Facilitate the Virus Replication

Abstract: Foot-and-mouth disease (FMD) is a severe, highly contagious viral disease of cloven-hoofed animals. In order to establish an infection, the FMD virus (FMDV) needs to counteract host antiviral responses. Tumor progression locus 2 (TPL2), a mitogen-activated protein kinase, can regulate innate and adaptive immunity; however, its exact mechanisms underlying TPL2-mediated regulation of the pathogenesis of FMDV infection remain unknown. In this study, we confirmed that TPL2 could inhibit FMDV replication in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Our results showed that VP1 could trigger part of innate immune pathways such as NF-κB pathway, toll-like receptor pathway, RIG-Ilike receptor pathway, and so on. The results were consistent with recent studies which found that VP1 proteins could inhibit the production of IFN-I in cells by binding to sorcin protein and TPL2 protein (19)(20)(21). In addition, VP1 protein also competitively binds to MAVS with TARF3 to inhibit the innate immune response (22).…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that VP1 could trigger part of innate immune pathways such as NF-κB pathway, toll-like receptor pathway, RIG-Ilike receptor pathway, and so on. The results were consistent with recent studies which found that VP1 proteins could inhibit the production of IFN-I in cells by binding to sorcin protein and TPL2 protein (19)(20)(21). In addition, VP1 protein also competitively binds to MAVS with TARF3 to inhibit the innate immune response (22).…”
Section: Figuresupporting
confidence: 92%
“…Studies have found that VP1 protein promotes host cells apoptosis by inhibiting the activation of the AKT pathway (18). It inhibits the production of IFN-I in cells by binding to sorcin protein and TPL2 protein (19)(20)(21). Besides, VP1 protein also competitively binds to MAVS with TARF3 to suppress the innate immune response, but the VP1 (E83K) mutation appears losing of this competitive inhibitory ability during the culture process (22).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, by conducting enrichment analysis, we explained the molecules potentially interacting with TMEM91 are mainly involved in response to interferon − beta/regulation of viral entry into host cell/modulation by symbiont of entry into host /regulation of viral genome replication/negative regulation of viral process/type I interferon signaling pathway. These processes also indicated the signi cant involvement of TMEM91 in the progression of tumors [25][26][27][28][29] , by reading the literature. Then, we identi ed the relationship between TMEM91 expression and medication response.…”
Section: Discussionmentioning
confidence: 93%
“…In countries that “live” with the disease, immunization methods have been studied through inoculation twice a year, with a cocktail vaccine containing the specific serotypes circulating locally. The VP1 capsid protein has been proposed by molecular studies as a significant immunogenic site and tested for vaccines with encouraging results [ 25 ]. Recently, the first report on the genetic and antigenic variation of FMD virus during virus persistence in cattle and domestic Asian buffalo was published.…”
Section: Foot and Mouth Disease (Fmd)mentioning
confidence: 99%